FRI0605 The use of hand perfusion scintigraphy to assess raynaud's phenomenon associated with hand-arm vibration syndrome. (15th June 2017) - Lee, KA; Chung, HW; Lee, S-H; Kim, H-R
Abstract : Background: Raynaud's phenomenon (RP) is a prominent manifestation of hand-arm vibration syndrome (HAVS). Previous studies have evaluated the diagnostic validity and characteristics of hand perfusion scintigraphy. However, no study to date has classified or differentiated the findings of this technique based on the aetiology of RP. Objectives: This study aimed to evaluate the hand perfusion scintigraphic features of hand-arm vibration syndrome (HAVS) and to compare these with the features of primary and secondary Raynaud's phenomenon (RP) associated with connective tissue disease (CTD). Methods: Hand perfusion scintigraphy was performed in 57 patients with primary RP, 71 patients with HAVS-related RP, and 36 patients with CTD-related RP. We calculated 6 ratios by using the time-activity curve and static blood pool images, the chilled to ambient hand and wrist ratios of the first peak height, initial slope, and blood pool uptake. We analysed 3 morphologic characteristics: slow progress pattern, paradoxically increased uptake pattern in the time-activity curve, and the inhomogeneous radioactivity uptake in the blood pool image. Results: All of the 71 patients with HAVS-related RP were mine workers. The onset of RP after exposure to vibration was at 21.8±7.3 years, with 26.3±7.0 years of vibration exposure time. The chilled to ambient hand ratios of the first peak height and the initial slope were significantly lower in patients with HAVS-related occupational RP than in patients with primary RP. The presence of a paradoxically increased uptake pattern was significantly lower in HAVS than in primary RP. Conclusions: There were significant differences in hand perfusion scintigraphic features between primary RP and HAVS. These results suggest that the underlying pathophysiology of the two diseases differs; thus, different criteria might be applied for their evaluation References: Palmer KT, Bovenzi M. Rheumatic effects of vibration at work. Best Pract Res Clin Rheumatol 2015;29:424–39. Acknowledgements: The author(s) received no financial support for the research, authorship, and/or publication of this article. Disclosure of Interest: None declared